Biology - Mader, Sylvia S. ([S.l.] : William C Brown Pub, 1993)
This is an introductory biology text which covers all areas of biology from the cell to animal behaviour. Also available are six "splits" of this book to allow easier purchase and staggered learning and understanding. Each "split" concentrates on a particular aspect of biology.
Keywords: biology